Swedish Universities in Transition: From "Mode 1" to what? - Hans Westlund (European Regional Science Association (ERSA), 2011)
This paper aims at analyzing the obstacles to in-depth cooperation between Swedish universities and other parts of society. Social capital is used as a comprehensive concept for the norms, values and relations that exist in the university sector and between this sector and the surrounding society. A working hypothesis is that universities' social capital is adapted by tradition to then Mode 1 production of knowledge, and that a transition to Mode 2 therefore requires a comprehensive change in the universities' social capital. After an introduction, section 2 gives a background in its description of the development of the Swedish university policy, mainly from a national perspective. In section 3 an analysis is made of the reasons why Swedish universities still mainly are dominated by Mode 1 production of knowledge and in section 4, a number of areas that deserve further illumination are given prominence. In both these sections, norms, values and networks are central concepts in the analysis. Together these phenomena form the social capital of the universities and between the universities and other parts of society and the conclusion is that this constitutes an important obstacle to the development of a Mode 2 production of knowledge in Sweden.
Keywords: 330